Geological characteristics of the Cua Dai beach zone by geophysical data and the relation to the regional accretion - erosion phenomenon - Duong Quoc, Hung; Nguyen Van, Diep; Mai Duc, Dong; Ngo Bich, Huong; Dang Xuan, Tung (Vietnam Journal of Marine Science and Technology, 2023)
This study presents some research results on the relationship between the geological environment of the surface layer and the level of modern tectonic activity in the sea waters of the Hoi An - Cua Dai area based on the interpretation of high-resolution shallow seismic data combined with the surface sediments’ grain-size analysis and other available data sources. The results show that the surface geological environment in the coastal waters North of the Thu Bon river fault is influenced by modern tectonic activities, believed to be a part of causing geological catastrophic events.